Peningkatan Hasil Belajar Materi Bangun Datar Menggunakan Papan Berpaku SD Negeri 2 Tlogopucang Tahun Ajaran 2017/2018 - Indra Rukmana (Universitas PGRI Semarang, 2019)
The results of preliminary observations at SD Negeri 2 Tlogopucang found problems in learning Mathematics in Flat Build Material. Teachers dominate more and involve students less in the learning process. If we observe the current learning, the teacher has not managed the class well. The teacher has not used the right learning model. Students are less active in learning, the research used is Classroom Action Research which consists of two cycles. In each cycle two meetings were held. Data collection uses observation sheets and by conducting evaluation tests. Data analysis techniques use qualitative and quantitative analysis. The results of the pre-cycle research, the average grade of 61 with a percentage of graduation 50%, students complete learning 8 children, students have not completed 8 children, the percentage of 50%. In cycle 1, it was obtained the average grade of 76, the percentage of completeness 65.75% the number of students who had completed learning 11 children, not yet completed learning a total of 5 children with a percentage of 35.25%. In cycle 2, all students meet the minimum completeness criteria, a percentage of 100% is obtained with an average grade of 96.25. The conclusion is the use of nail board media can improve the learning outcomes of students in class II of SDN 2 Tlogopucang in the academic year 2017/2018.